Pengaruh iklan lucu terhadap sikap dan kepercayaan pengguna di Kuching, Sarawak - Mohd Faizal, Nawawi. (Universiti Malaysia Sarawak, UNIMAS, 2009)
The objectives of this research are to study whether humor advertisements will influence the consumer attitud es and beliefs and also their response towards that advertised products. Beside that, it also to study whether the different races will influences the consumers’ response toward that product. The s cope of this study is limited by the Kuching people only. A total of 430 questionnaires were distributed, however, there were only 385 questionnaires collected. Other than that, from the Correlation analysis, it shows that consumer attitude and belief towards the humor advertisements will influences their response toward that product. However, from ANOVA, it shows that there are no different significant among the races. Because of that, this study shows that attitude, belief, and response of the consumers are the most important thing to an advertisement because wit hout this three factors, percentage of the advertisement to success are very low. From the discussion of this study, marketers should to be more focus to all of these factors while producing an advertisement and not only based on the different races of the consumers